KEJADIAN KETUBAN PECAH DINI DAN KEJADIAN ASFIKSIA PADA BAYI BARU LAHIR - Istiqomah, Shufiatul; Arum, Dyah Noviawati Setya; Widyastuti, Yani (Poltekkes Kemenkes Yogyakarta, 2013)
Neonatal mortality worldwide approximately 23% are caused by asphyxia. The cause of asphyxia and premature rupture of membranes (PROM) is one of the causes of asphyxia especially in Indonesia. Moreover, Gunungkidul district showed the highest numbers of infant death in DIY (Yogyakarta). In regional general hospital (RSUD) Wonosari there was an increasing PROM incidence in the period of 2010-2012. This is followed by the increased of asphyxia. The research employee observational methods, with retrospective cohort design. This research was done in the RSUD Wonosari with purposive sampling. The research subject was the maternity from January, 1st to December 31st 2012 which into 2 groups, the exposed groups (women giving birth with PROM) and the unexposed group (women giving birth with no PROM). Hypothesis test using Chi-square test. As much as 50.8% maternal with PROM giving birth asphyxia. The significance value is 0.00 (p-value<0.05) then there is a relationship between the occurrence of events PROM with asphyxia with RR 2.3 95% CI (1.54-8.89). Genesis PROM increased 2.3 time of asphyxia risk in newborn.